SAT0329 Scleroderma in Men in Northwestern Spain: Differentiating Clinical Features. (10th June 2014) - Freire, M.; Gόmez-Sousa, J.; Val, N.; Baroja, A.; Alonso, M.; Sousa, A.; Soto, A.; Rivera, A.; Sopeña, B.
Abstract : Background: 85-90% of patients with systemic sclerosis (SSc) are women, so there are few series that have evaluated distinguishing clinical features in men (1). Objectives: To describe clinical features of the male subgroup of a cohort of patients diagnosed with scleroderma in our hospital and evaluate the differences within the female subgroup. Methods: Encoded patients with diagnosis of SSc in our hospital from 1985 until December 2013 were collected. They were classified into four groups using a modification of LeRoy and Medsger proposed criteria (2): diffuse systemic sclerosis (dcSSc), limited systemic sclerosis (lcSSc), systemic sclerosis sine scleroderma (ssSSc) and pre-scleroderma (pre-SSc). Medical records were reviewed, recording clinico-epidemiological data and results of immunological tests. Results: Of the 114 patients diagnosed with SSc in this period, 17 (15%) were male, the group described below: 10 (59%) were classified as dcSSc and 7 (41%) as lcSSc. Mean age at diagnosis was 49 years. 9 (53%) had a history of exposure to SSc related toxic - 8 silica, 1 vinyl chloride-. All patients had positive ANA, 3 ACA, 8 Scl70, 3 dsDNA, 2 antiRo, 1 antiLa, 1 antiRNP and 1 antiSm. Capillaroscopy was performed in 3 patients (18%), finding a scleroderma pattern throughout, with a presence in all three of giant capillaries and capillary loss and ramified capillaries in two. Along the follow-up (mean 11 years), 15 patients (88%) had Raynaud's phenomenon, 10 (59%), dyspnea, 9 (53%) ulcers, 7 (41%) telangiectasia, and 4 (23%) digestive disorders. Interstitial lung disease was documented in 10 patients (55%) and PAH in 3 (16%). 12 patients (71%) died during the monitoring, an average of 10 years after initial diagnosis. The cause of death was: respiratory failure in 4 (33%), heart failure in 2 (17%), carcinoma in 3 (25%), cirrhosis in 1 (8%) and unknown in 2 (17%). Multivariate analysis comparing men with women subgroup, showed in male less age at diagnosis (p 0.017) and death (p 0.001), a predominance therein of exposure to toxic (p 0.05), dcSSc (p 0.003), Scl70 positivity (p 0.004), interstitial lung disease (p 0.002), and presence of giant capillaries (p 0.05), capillary loss (p 0.02) and ramified capillaries (p 0.003) in nailfold capillaroscopy. No statistically significant difference was found in mortality or survival time from diagnosis. Conclusions: 1. In more than half of our male patients with SSc, a related toxic was found, mainly silica. 2. Our male subgroup was differentiated clinically in an younger occurrence of the disease, a predominance of dcSSc, positivity for Scl70, presence of interstitial lung disease, and advanced endothelial damage capillaroscopic patterns. References: J.-B. Gaultier et al. Systemic sclerosis in men. La Revue de médecine interne 2008: 181–186. LeRoy EC, Medsger TA, Jr. Criteria for the classification of early systemic sclerosis. J Rheumatol. 2001;28(7):1573-6. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2014